1999
DOI: 10.1007/pl00009422
|View full text |Cite
|
Sign up to set email alerts
|

All Polytopes Are Quotients, and Isomorphic Polytopes Are Quotients by Conjugate Subgroups

Abstract: In this paper it is shown that any (abstract) polytope P is a quotient of a regular polytope M by some subgroup N of the automorphism group W of M, and also that isomorphic polytopes are quotients of M by conjugate subgroups of W . This extends work published in 1980 by Kato, who proved these results for a restricted class of polytopes which he called "regular". The methods used here are more elementary, and treat the problem in a purely nongeometric manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 8 publications
0
67
0
Order By: Relevance
“…Given a 4-orbit toroidal map, the minimal regular cover and the minimal rotary cover may or may not coincide; this depends on γ. For example, the minimal regular and minimal rotary covers of the map {4, 4} (2,1), (7,0) coincide. On the other hand, the covers of {4, 4} (4,3),(5,0) = {4, 4} (4,3),(−1,3) are distinct (see Figure 2 (a)).…”
Section: Maps Of Type {4 4}mentioning
confidence: 99%
See 1 more Smart Citation
“…Given a 4-orbit toroidal map, the minimal regular cover and the minimal rotary cover may or may not coincide; this depends on γ. For example, the minimal regular and minimal rotary covers of the map {4, 4} (2,1), (7,0) coincide. On the other hand, the covers of {4, 4} (4,3),(5,0) = {4, 4} (4,3),(−1,3) are distinct (see Figure 2 (a)).…”
Section: Maps Of Type {4 4}mentioning
confidence: 99%
“…However, equivelar toroidal maps can be covered by smaller maps that also have high degrees of symmetry. Notably, each equivelar toroidal map has a unique finite minimal regular cover (see [7], [14]). …”
Section: Introductionmentioning
confidence: 99%
“…In [9] it is shown that any polytope Q may be written in the form P/N for some regular polytope P and some subgroup N of the automorphism group of P. These subgroups N of Γ(P) = ρ 0 , . .…”
Section: Chiral Polytopes As Quotients Of Regular Onesmentioning
confidence: 99%
“…The polytope K is isomorphic to the quotient P/N where N is the stabilizer in Γ(P) of a flag of K. Here P/N can be thought of as the combinatorial structure resulting from identifying the image Φw of the base flag Φ with all flags of the form Φhw where h ∈ N , for every w in the monodromy group. We refer to [22] and [37, Section 2D] for more information on flag actions and quotients.…”
Section: Group Structuresmentioning
confidence: 99%